Optimal advertising and pricing decisions for complementary products - Ata Allah Taleizadeh; Masoud Charmchi (Journal of Industrial Engineering International, 2015)
Cooperative advertising is an agreement between a manufacturer and a retailer to share advertising cost at the local level. Previous studies have not investigated cooperative advertising for complementary products and their main focus was only on one good. In this paper, we study a two-echelon supply chain consisting of one manufacturer and one retailer with two complementary goods. The demand of each good is influenced not only by its price but also by the price of the other product. We use two game theory approaches to model this problem; Stackelberg manufacturer and Stackelberg retailer.
Keywords: 650; Pricing; Advertising; Game theory; Supply chain; Complementary; Stackelberg